SEQUENTIAL DELIVERY OF CRYOGEL RELEASED GROWTH FACTORS AND CYTOKINES ACCELERATES WOUND HEALING AND IMPROVES TISSUE REGENERATION - Jimi, Shiro; Jaguparov, Alexandr; Nurkesh, Ayan; Sultankulov, Bolat; Saparov, Arman (Frontiers in Bioengineering and Biotechnology, 2020)
Growth factors and cytokines that are secreted by cells play a crucial role in the complex physiological reaction to tissue injury. The ability to spatially and temporally control their actions to maximize regenerative benefits and minimize side effects will help accelerate wound healing and improve tissue regeneration. In this study, the sequential targeted delivery of growth factor/cytokine combinations with regulatory functions on inflammation and tissue regeneration was examined using an internal splint wound healing model. Four examined growth factors and cytokines were effectively incorporated into a novel chitosan-based cryogel, which offered a controlled and sustained release of all factors while maintaining their biological activities. The cryogels incorporated with inflammation modulatory factors (IL-10 and TGF-β) and with wound healing factors (VEGF and FGF) were placed on the wound surface on day 0 and day 3, respectively, after wound initiation. Although wound area gradually decreased in all groups over time, the area in the cryogel group with growth factor/cytokine combinations was significantly reduced starting on day 7 and reached about 10% on day 10, as compared to 60–65% in the control groups. Sequential delivery of inflammation modulatory and wound healing factors enhanced granulation tissue formation, as well as functional neovascularization, leading to regenerative epithelialization. Collectively, the chitosan-based cryogel can serve as a controlled release system for sequential delivery of several growth factors and cytokines to accelerate tissue repair and regeneration.
Keywords: Type of access: Open Access; Cryogel; Tissue Regeneration